The Relationship of Willingness to Learn And Encouragement of Parents With Medical Surgical Nursing Learning Achievement in The Undergraduate Nursing Program of Nahdlatul Ulama University, Surabaya - Tria Wahyuningrum; Ridanau Arisna Safitri (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The Relationship of Willingness to Learn And Encouragement of Parents With Medical Surgical Nursing Learning Achievement in The Undergraduate Nursing Program of Nahdlatul Ulama University, SurabayaThere are two types of elements that affect motivation: extrinsic and intrinsic factors. The challenge in this thesis is restricted to extrinsic factors—parental encouragement—and intrinsic factors—learning readiness. Based on the preliminary statistics, the average MEDICAL SURGICAL NURSING value for the previous three years was low, at 0.68%. The purpose of the study is to examine how parental support and learning readiness relate to MEDICAL SURGICAL NURSING learning achievement in UNUSA's Bachelor of Nursing programme. This study has an analytical design. There were 137 Bachelor of Nursing students in the class of 2011 during the fifth semester of the 2013–2014 academic year; 103 of them made up the sample. Proportionate stratified random sampling was employed in the sampling process. Parental encouragement and openness to learning are the independent variables. MEDICAL SURGICAL NURSING learning achievement is the dependent variable. A questionnaire was used to gather the data, which were then subjected to a univariate ANOVA test with a significance level of α < 0.05. The study's univariate ANOVA test findings revealed that = 0.009, which led to its rejection. This suggests that there was a strong correlation between MEDICAL SURGICAL NURSING learning achievement and parental encouragement and motivation to learn. The study's findings indicate that parental support and openness to learning are related to MEDICAL SURGICAL NURSING learning achievement in the UNUSA undergraduate nursing programme. Students' willingness to learn optimally must grow if they are to attain effective learning outcomes.